Structure, dynamics and hydration in drug-DNA recognition - Williams, Huw Edward Llewelyn (2001)
The role of deoxyribonucleic acids in the cell has made DNA an attractive target for drug molecules. The anthracycline antitumour antibiotics are potent cytotoxic agents that have found widespread use in cancer chemotherapy. Nogalamycin binds DNA through intercalation, preferentially to 5'-TpG and 5'-CpG sites, by threading through the DNA helix and interacting with both the major and minor grooves simultaneously. In this thesis, the interaction of nogalamycin with the 5'-TpG site has been investigated using synthetic oligonucleotide duplexes and a combination of high-resolution NMR techniques and NOE-restrained molecular dynamics simulations. The solution structure of the 1: 1 complex with d(ATGCAT)2 is described with NOE data unambiguously identifying the position and orientation of the bound drug molecule, allowing conclusions to be drawn regarding the specificity for the TpG site. Binding at one TpG site sterically blocks the interaction at the symmetrically equivalent CpA site. The structural studies are extended to investigate by NMR the role of solvation in drug- DNA recognition and binding. Based on the sign and magnitude of solute-solvent NOEs, it is shown that only a small subset of water molecules visible in the crystal and MD structures are found to be bound in the solution complex, and that a number of these are involved in mediating drug-DNA interactions. The role of the dynamic network of water molecules in stabilising the complex in solution is discussed. Finally, the binding of nogalamycin at a TpG site carrying a DNA strand break has been investigated using a novel designed single-stranded intermolecular duplex consisting of two hairpins stabilised by GAA loops [d(ACGAAGTGCGAAGC)]. Although stacking of the two hairpins is weak, nogalamycin is shown to bind and stabilise a 1: 1 complex by binding at the intercalation site. The complex is discussed in terms of the mechanism by which nogalamycin is able to bind to premelted duplex DNA.